REALISASI UNTUK SISTEM DESKRIPTOR LINIER INVARIANT WAKTU - Novrianti . (Jurnal Matematika UNAND, 2013)
A continuous invariant time linear control system is a model which is oftenapplied in economics, engineering, and numerical analysis. In this paper, the realizationof the transfer function for the descriptor system with multi inputs and multi outputs(MIMO) is discussed. Some algebraic techniques are used to prove some theorems andto get a realization of a transfer function.